Policy On The Implementation Of Restrictions On Community Activities (PPKM) Based On Inclusive Law - Muh Akbar Fhad Syahril; Ade Risna Sari; Fuad Fuad; Rachmadi Usman; Baren Sipayung (DE LEGA LATA: JURNAL ILMU HUKUM, 2023)
The COVID-19 pandemic that has hit the world has impacted the crisis in all aspects of human life. The COVID-19 pandemic, which was initially a health crisis, quickly transformed into an economic, social, political, and even environmental crisis. The Indonesian government is trying to control the spread of COVID-19 by issuing various policies, one of which is the Implementation of Community Activity Restrictions (PPKM). However, PPKM has attracted a lot of controversy because it is felt that it has made it difficult for many people in the context of mobility and seems to violate personal rights. This study aims to analyze PPKM policy with an inclusive legal approach. As part of the social order, in addition to norms of decency and religion, inclusive law protects and integrates the interests of members of society. This research method is normative-juridical with a statutory and conceptual approach. The data obtained are analyzed qualitatively and presented descriptively. The results showed that the PPKM policy is an effort to overcome the decline of society due to the pandemic and follows the concept of inclusive law. Between inclusive law and legal reality, there is a commonality in seeing the various interests of members of society that will create order in life. This makes people able to live with certainty and create order. The Indonesian government chose to seek an orderly situation by imposing a ban on mobility through PPKM